The Philosophy of the Cave: from Interpretation to Change of the World: “Ideology” and praxis in Antonio Gramsci’s Prison Notebooks - Gaboardi, Natalia (International Gramsci Journal, 2024)
Gramsci’s “philosophy of praxis” takes common sense, folklore, and religion as its starting point for understanding the various gnoseological dimensions (i.e., everything that is not directly related to one’s instinctive and unreflective existence). A study of the occurrences of the term “ideology” in the Prison Notebooks shows that the relationship between “conception of the world” and “philosophy” is one of the most original aspects of Gramsci’s thought in relation to the Marxist tradition. Moreover, the Gramscian concept of ideology helps us to rethink the link between theory and practice in a philosophical perspective.